Female entrepreneurship and SMEs: Changes in access to credit and business results? - Antonio Garcia-Tabuenca; Federico Pablo-Martí; Fernando Crecente-Romero (European Regional Science Association (ERSA), 2015)
The research on women entrepreneurship has mainly studied these topics: i) the characteristics and motivations (Brush and Hisrich, 1991; Pablo-Martí et al., 2014), ii) the strategic choice (Verheul et al., 2008), iii) the role of leadership (Schwartz, 1976; Justo et al. 2006)), iv) the entry barriers (Brush and Gatewood, 2008), mainly access to funding (Klapper and Parker, 2010), and v) the performance and achieved results (Coleman and Robb, 2009; Díaz and Jiménez, 2010; Crespo-Espert et al., 2012). These topics have been well studied. However, further research on this field is required. The long period of crisis from 2007 on has changed some of the findings related to these issues. This is especially significant in the most affected economies such as those of the southern countries of the EU. In these countries the severity of the crisis has had significant consequences for the productive sector (destruction of companies, high unemployment, credit restrictions) and on public finances under severe uncertainty (sovereign debt crisis, banking crisis). This is generating major changes in productive activity and business competitiveness, which is associated with the deleveraging of companies, as well as the varying prevalence of smaller companies (SMEs) in the economies. In this context, it may be hypothesized that the progress and results of activities led by women entrepreneurs had significant changes between the period before the crisis and the current stage of uncertain recovery. In this paper we analysed the dynamics and evolution of entrepreneurial activity of women in Spain in the period 2003-2013. It includes a stage of strong expansion and other recessive. Also, the research focuses on the differences found in two of the topics listed above: a) the obstacles in accessing to funding and b) the results of businesses women-owned compared to those of male-owned businesses. We made use of the SABI database. It includes information from the commercial registers. It has over one million companies with employees that represent most of the Spanish companies. The samples for this study differentiate whether the company is owned by a man or a woman. These samples are representative for company sizes, sectors and regions. Thus the results that adopt a regional approach can be segmented for a better understanding of the different types of women's businesses. The variables of the study are some financial indicators: credit ratio, debt ratio, productivity, EBITDA over assets, EBITDA over turnover, economic profitability and financial profitability. We employ various dummies to control for differences in size, sector and location of firms. The results allow understanding the different behaviour of women entrepreneurs and its reasons. They can also serve to develop new entrepreneurship policies related to gender in economic recovery.
Keywords: B54; M21; G30; 330; women entrepreneurs; credit; debt; business results; SMEs; business cycle